Circulations à la frontière entre Kurdes d’Irak et Kurdes d’Iran. - Cyril Roussel (EchoGéo)
On the outskirts of Iran, spaces as Iraqi Kurdistan – like in Dubai where the situation is well known - benefit of the protectionist policy of the Islamic Republic and the cross-border differential to implement a significant illegal trade. The created wealth then generated a whole reorganization of the border-area. It has also created a set of chains of actors sometimes very complex, where economic and political interests often remain intertwined.